Red and Blue Nation? : Consequences and Correction of America's Polarized Politics - Brady, David W.; Nivola, Pietro S. (Book collections on Project MUSE., 2008)
America's polarized politics are largely disconnected from mainstream public preferences. This disconnect poses fundamental dangers for the representativeness and accountability of government, as well as the already withering public trust in it. As the 2008 presidential race kicks into gear, the political climate certainly will not become less polarized. With important issues to address--including immigration policy, health care, and the funding of the Iraq War--it is critical that essential policies not be hostage to partisan political battles. Building upon the findings of the first volume of Red and Blue Nation? (Brookings, 2006), which explored the extent of political polarization and its potential causes, this new volume delves into the consequences of the gulf between "red states" and "blue states." The authors examine the impact of these political divisions on voter behavior, Congressional law-making, judicial selection, and foreign policy formation. They shed light on hotly debated institutional reform proposals--including changes to the electoral system and the congressional rules of engagement--and ultimately present research-supported policies and reforms for alleviating the underlying causes of political polarization. While most discussion of polarization takes place in separate spheres of journalism and academia, Red and Blue Nation? brings together a unique set of voices with a wide variety of perspectives to enrich our understanding of the issue. Written in a broad, accessible style, it is a resource for anyone interested in the future of electoral politics in America.